Mob war - Ingvordsen, J. Christian; La Motta, Jake; Shapiro Glickenhaus Entertainment; Cinetel Films ([New York, N.Y.] : Shapiro Glickenhaus Entertainment, 1989)
When John Falcone meets Todd Barrett, it's a match of strength against wits. Falcone is the undisputed boss of New York's underworld. Barrett is the media mastermind whose genius for public relations has made his clients rich and celebrated. When Barrett agrees to work for Falcone, it could be a match made in heaven, or one made in hell.
Jake La Motta, Johnny Stumper, David Henry Keller, John Rano, John Christian.
Director of photography and editor, Steven Kaman; music, Christopher Burke.
In English or Spanish.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed August 7, 2015)
Keywords: Drug traffic -- New York (State) -- New York -- Drama; Mafiosi -- New York (State) -- New York -- Drama; Action and adventure films; Gangster films; Feature films; Internet videos; Streaming video